2012
DOI: 10.1101/gr.142802.112
|View full text |Cite
|
Sign up to set email alerts
|

Microsporidian genome analysis reveals evolutionary strategies for obligate intracellular growth

Abstract: Microsporidia comprise a large phylum of obligate intracellular eukaryotes that are fungal-related parasites responsible for widespread disease, and here we address questions about microsporidia biology and evolution. We sequenced three microsporidian genomes from two species, Nematocida parisii and Nematocida sp1, which are natural pathogens of Caenorhabditis nematodes and provide model systems for studying microsporidian pathogenesis. We performed deep sequencing of transcripts from a time course of N. paris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
320
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(342 citation statements)
references
References 64 publications
19
320
2
1
Order By: Relevance
“…Such diversity could be related to the fact that A. algerae is able to infect both mammals and insect hosts. This diversity also suggests an increased host dependency, which is not in accordance with O. bayeri proteomic data, and suggests an increased genome complexity related to reduced host dependency 16 . Furthermore, the metabolic patterns of how the insect and mammalian stages of the parasite acquire amino acids and other nutrients are unknown, suggesting that the detected transporter genes need to be elucidated by further bench work on the precise metabolic pathways.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Such diversity could be related to the fact that A. algerae is able to infect both mammals and insect hosts. This diversity also suggests an increased host dependency, which is not in accordance with O. bayeri proteomic data, and suggests an increased genome complexity related to reduced host dependency 16 . Furthermore, the metabolic patterns of how the insect and mammalian stages of the parasite acquire amino acids and other nutrients are unknown, suggesting that the detected transporter genes need to be elucidated by further bench work on the precise metabolic pathways.…”
Section: Discussionmentioning
confidence: 55%
“…Such sequence variability has also been previously observed by sequencing cloned PCR products from A. algerae and also A. locustae 35 . Sequence polymorphisms have recently been described in the Nematocida genus 16 . Indeed, these authors have identified SNPs preferentially located in coding regions that generate synonymous codons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Homologs of genes involved in conserved biochemical pathways are few in microsporidia compared with other eukaryotes; a feature that highlights their dependence on host cells for metabolic supplies . Finally, most genome studies of species with mononucleated spores have revealed evidence of diploidy in microsporidia (Katinka et al, 2001;Cuomo et al, 2012;Selman et al, 2013;Desjardins et al, 2015;Watson et al, 2015), although recent analyses of diplokaryotic species have suggested that polyploidy can also occur in this group (Pelin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%